A Study on the Causes and Intervention of Job Burnout of Young Teachers in Chinese Vocational Colleges (Journal of Namibian Studies : History Politics Culture, 2023)
During the course of the study, the researcher identifies the numerous elements that contribute to job burnout among young teachers in higher vocational institutions in Guangxi and proposes intervention strategies for focused improvement. The author utilizes policy tools to examine the consequences of my nation's education policies and make references to constructive recommendations on human capital management in high vocational colleges. As research objects, ten institutions of higher vocational education are selected. Then, distribute the questionnaires according to the ratio of young teachers in each school to the total number of young instructors in these 10 vocational schools. 350 educators were chosen at random for this study. Statistically, the Total Effect of Transactional Psychological Capital (Personal Factors) on Professional Values (.594) is bigger than the Effect of Cognitive Social Capital (.593). (School Factor). In addition, Perceptual behavior control has an effect (0.394) on Professional values. Statistically, the Total Effect of Perceptual Behavior Control on Burnout (0.614) is larger than Interpersonal Psychological Capital (Personal factors). It should also be explored how demographic and environmental factors influence Transactional psychological capital, Cognitive social capital, Perceptual behavior control, Interpersonal psychological capital, Professional values, and Burnout.